Analisis Sanitasi Lingkungan terhadap Gejala ISPA di Kecamatan Tuah Madani - Rasyid, Zulmeliza; Susanti, Nurvi (Journal of Religion and Public Health, 2024)
Symptoms of ARI are symptoms of infection that affect the respiratory tract, both the upper (such as the nose and throat) and the lower (such as the bronchi and lungs) including cough, runny nose, sore throat, fever, shortness of breath (in more severe cases). ARI can be caused by various pathogens, including viruses, bacteria, and fungi. and can affect anyone, especially children and the elderly. This study is quantitative with Cross-sectional Design. The sample consisted of 150 houses. The location of the study was in Tuah Madani District. The research variables included clean water sources, waste management, waste water drainage channel and housing density. Data collection was by observation and questionnaire distribution. Data collection techniques were quota sampling. Data were processed by computerization. Univariate and bivariate data analysis used the chi-square test. The results of the study showed that there was a relationship between access to clean water (p-value 0.0001), waste management (p-value 0.0001), waste water drainage channel (p-value 0.0001) and housing density (p-value 0.001). It is expected that the agency will provide counseling to the community through health promotion activities regarding access to clean water, waste management, waste water drainage channel, and housing density that meets health requirements as well as prevention and control of ARI. Keywords: ARI Symptoms,  Environment, Sanitation.